Modified binder for dry-method electrode, dry-method electrode pole piece and preparation method of dry-method electrode pole piece
By using polycyclic aromatic hydrocarbon alkali metal reagents to modify polytetrafluoroethylene (PTFE) and destroying the C-F bonds in PTFE, the problems of insufficient viscoelasticity and reduced first efficiency of dry electrodes are solved, and higher battery performance and Lower manufacturing costs.
Patent Information
- Application Number
- CN202411478013.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The wet coating process of traditional lithium-ion batteries has problems such as large solvent usage, high energy consumption, high production costs, and solvent residue affecting battery life, and the wet process has reached the limit of energy density.
Polytesylinylin (PTFE) is used as a bonding agent for drying method, and PTFE is immersed in polygon aromatic hydrocarbon alkaline reagents generated by reacting polygon aromatic and alkaline metal reactions to destroy the C-F key in PTFE, modified PTFE PTFE The surface characteristics to improve their adhesion.
The adhesion of the modified PTFE has been improved, enhanced the binding force between the conductive and the streaming, reducing the side effects of the interface, improved the first effect and cycle stability of the battery, and simplified the process, reduced the manufacturing cost, and reduced the manufacturing cost Essence
Smart Images

Figure CN119351005A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a modified binder for dry-process electrodes, a dry-process electrode pole piece, and a preparation method thereof. Background Art
[0002] Among many secondary batteries, lithium-ion batteries are widely used in power energy and electronics fields due to their advantages such as high energy density, long cycle life and high conversion efficiency. As the main component of the battery, the electrode accounts for about 1 / 3 of the production cost, which has a huge impact on battery performance. At present, traditional lithium-ion batteries usually prepare electrodes through a wet coating process. N-methyl-2-pyrrolidone (NMP) or deionized water is required as a solvent during the homogenization process. After the coating is completed, it takes a lot of time and energy to dry and remove the solvent, which greatly increases energy consumption and production costs. The solvent components are easy to remain in the electrode coating and cause side reactions, thereby affecting the service life of the battery; in addition, since the NMP solvent has certain toxicity, a recovery and reprocessing device needs to be added, otherwise it will cause pollution to the environment, further increasing the manufacturing cost. The most important thing is that the wet coating process has reached its limit in improving the energy density of the battery.
[0003] Compared with the wet coating process, the dry molding process using polytetrafluoroethylene (PTFE) as a binder has more advantages in the preparation of electrode plates: since no solvent is used in the entire preparation process, PTFE is transformed into fibers under the action of high shear force to wrap the active materials together, and the bonding force is much greater than that of traditional organic binders. The surface density of the prepared electrode can be increased by about 20% compared with the traditional wet electrode. However, PTFE has limited ion conductivity, and due to its limited viscoelasticity, it cannot ensure sufficient interface adhesion between the active material and the conductive carbon and the current collector, which will cause the active material to form gaps during volume expansion / contraction, and the active material will fall off, thereby reducing the battery capacity and cycle stability.
[0004] In addition, since PTFE contains CF bonds, it can react with lithium during charging, thereby consuming some lithium ions, reducing the initial efficiency of the battery, and causing capacity loss. The side reaction products formed will also affect the subsequent cycle stability of the battery.
[0005] Current research mainly focuses on PTFE modification or the use of other binders to improve this problem.
[0006] For example, some related technologies provide a new binder formula, which includes a main binder and a glue containing a dispersible binder and an aqueous binder. The main binder is first dry-mixed with the raw material to form a first dry material, and then the glue is added for dispersion. The obtained second dry material is crushed to obtain a powder after the main binder is fiberized. The powder can be calendered to produce a dry electrode. This method requires the introduction of a small amount of additional solvent and requires two crushings. The process is more complicated and the manufacturing cost is increased.
[0007] Other related technologies provide a method for preparing a composite binder for dry electrodes: using a hydrophilic conductive carbon material and deionized water to form a uniform slurry, then mixing it with a PTFE dispersion stock solution, breaking the emulsion and condensing it, and obtaining a composite polytetrafluoroethylene dispersion resin. The hydrophilic modification treatment method is a heat treatment method or a liquid phase treatment method; the heat treatment method is to calcine the conductive carbon at 450°C; the liquid phase treatment method is to immerse the conductive carbon in a H2O2, H2SO4 or HNO3 solution. The process flow is relatively complicated, and due to the additional introduction of a demulsifier, it is easy to form residues in the electrode and produce side reactions with the electrolyte in the later electrochemical process, affecting the battery capacity and cycle stability.
[0008] Therefore, there is an urgent need to develop a dry electrode modification binder that has good adhesion with both the conductive agent and the current collector, can reduce side reactions and thus inhibit the reduction of the first efficiency, and has a relatively simple process. Summary of the invention
[0009] The embodiments of the present application provide a modified binder for dry electrodes, a dry electrode pole piece and a preparation method to solve the problems of insufficient viscoelasticity after using PTFE as a pole piece binder in the related art, reduced first efficiency due to the introduction of CF bonds, and decreased cycle stability.
[0010] In a first aspect, a method for preparing a modified binder for a dry electrode is provided, comprising:
[0011] The polycyclic aromatic hydrocarbons are dissolved in a non-protonic polar solvent, and an alkali metal is added to generate a polycyclic aromatic hydrocarbon alkali metal reagent;
[0012] The polytetrafluoroethylene is immersed in the polycyclic aromatic hydrocarbon alkali metal reagent to be modified; the polytetrafluoroethylene immersed in the polycyclic aromatic hydrocarbon alkali metal reagent is washed with a non-protonic polar solvent, and then heated and dried to obtain modified polytetrafluoroethylene powder.
[0013] In some embodiments, the polycyclic aromatic hydrocarbons include one or more of naphthalene, biphenyl, biphenyls, and condensed ring aromatic hydrocarbons.
[0014] In some embodiments, the aprotic polar solvent includes one or more of dimethylformamide, dimethyl sulfoxide, acetone, tetrahydrofuran and dimethyl ether.
[0015] In some embodiments, the alkali metal includes one or more of lithium metal, sodium metal, and potassium metal.
[0016] In some embodiments, the concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.1-2 mol / L.
[0017] In some embodiments, the concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.3-1.5 mol / L.
[0018] In some embodiments, the immersion time of the polytetrafluoroethylene is 1 to 5 minutes.
[0019] In some embodiments, during heating and drying, the heating temperature is 100-120° C., and the heating time is 6-12 hours.
[0020] In a second aspect, a modified binder for a dry-process electrode is provided, which is prepared by any of the above-described methods for preparing a modified binder for a dry-process electrode.
[0021] In a third aspect, a method for preparing a dry electrode sheet is provided, comprising:
[0022] Premixing the electrode active material, the conductive agent and the modified binder for the dry electrode as described above to obtain a premixed powder;
[0023] The premixed powder is subjected to fibrillation treatment to obtain a fiberized material;
[0024] The fiberized material is pressed into a film by hot rollers, and then thinned and rolled into a pole film;
[0025] The electrode film and the current collector are composited by hot rolling to obtain a dry electrode electrode.
[0026] In some embodiments, calculated by mass fraction, the electrode active material is 80% to 99%, the conductive agent is 0.5% to 10%, and the modified binder is 0.5% to 10%.
[0027] In some embodiments, the electrode active material is a positive electrode active material or a negative electrode active material.
[0028] In some embodiments, the positive electrode active material includes a mixture of one or more of lithium iron phosphate LFP, lithium iron manganese phosphate LFMP, lithium nickel cobalt manganese oxide NCM, lithium cobalt oxide LCO, lithium nickel manganese oxide LNMO and lithium-rich manganese-based LRM.
[0029] In some embodiments, the negative electrode active material includes one or more of graphite or silicon carbon.
[0030] In some embodiments, the conductive agent includes one or more of carbon nanotubes CNT, acetylene black, SuperP, Ketjen black, MXene and graphene.
[0031] In some embodiments, during premixing, the rotation speed is 1000-2500 rpm, and the mixing time is 10-30 min.
[0032] In some embodiments, a jet mill is used for fibrillation treatment, the air flow pressure during feeding of the jet mill is 0.6-0.8 MPa, the crushing pressure is 0.4-0.6 MPa, and the crushing pressure varies from large to small.
[0033] In some embodiments, the roller surface temperature during the hot rolling film forming and thinning process is 60-150°C, the rolling pressure is 200-2000kg, and the thickness of the thinned electrode film is 50-300um; the hot rolling film forming and thinning process includes one or more of transverse rolling, longitudinal rolling, and alternating transverse and longitudinal directions.
[0034] In some embodiments, the temperature during the hot roller lamination process is 80-200° C., and the pressure is 200-2000 kg.
[0035] In a fourth aspect, a dry electrode plate is provided, which is prepared by any of the above-described methods for preparing a dry electrode plate.
[0036] In a fifth aspect, a secondary battery is provided, which includes the dry electrode plate as described above.
[0037] The beneficial effects of the technical solution provided by this application include:
[0038] The embodiment of the present application provides a modified binder for dry electrode, dry electrode pole piece and preparation method. When polytetrafluoroethylene is added to polycyclic aromatic hydrocarbon alkali metal reagent and soaked, the alkali metal ions in the polycyclic aromatic hydrocarbon alkali metal reagent can destroy the CF bond in polytetrafluoroethylene PTFE, remove some fluorine atoms on the surface of polytetrafluoroethylene PTFE, and leave a carbonized layer and some oxygen-containing functional groups on the surface, including polar groups such as hydroxyl, carbonyl and unsaturated bonds. These groups can increase the surface energy, reduce the contact angle, and improve the wettability, thereby improving the adhesion of the modified PTFE. When preparing the dry electrode pole piece, it enhances the bonding force between it and the conductive agent and the current collector, and improves the problem of insufficient viscoelasticity of PTFE in the dry pole piece. At the same time, the present application destroys some CF bonds in polytetrafluoroethylene PTFE in advance through modification means, thereby reducing the generation of interface side reaction products, improving the problem of reduced first effect of dry electrode, and improving battery cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 A flow chart of a method for preparing a modified binder for a dry electrode provided in an embodiment of the present application;
[0041] Figure 2 A schematic diagram of the structural changes of PTFE during the modification process provided in the embodiments of the present application;
[0042] Figure 3 A comparison chart of the shear strength of modified PTFE provided in the examples of the present application;
[0043] Figure 4 A comparison chart of the contact angles of modified PTFE provided in the examples of the present application;
[0044] Figure 5 A flow chart of the method for preparing a dry electrode plate provided in an embodiment of the present application. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0046] See also Figure 1 As shown, the embodiment of the present application provides a method for preparing a modified binder for a dry electrode, which comprises the following steps:
[0047] 101: Dissolve polycyclic aromatic hydrocarbons in a non-protonic polar solvent and then add an alkali metal to generate a polycyclic aromatic hydrocarbon alkali metal reagent.
[0048] In step 101, the reaction may be carried out under the protection of an inert gas such as nitrogen or argon, and the polycyclic aromatic hydrocarbon alkali metal reagent finally obtained belongs to a polycyclic aromatic hydrocarbon-alkali metal complex.
[0049] The polycyclic aromatic hydrocarbons have a variety of optional substances. For example, as an example, the polycyclic aromatic hydrocarbons include one or more of naphthalene, biphenyl, biphenyls, and condensed aromatic hydrocarbons.
[0050] The aprotic polar solvent has a variety of optional substances. For example, as an example, the aprotic polar solvent includes one or more of dimethylformamide, dimethyl sulfoxide, acetone, tetrahydrofuran and dimethyl ether.
[0051] The alkali metal has a variety of optional substances, for example, as an example, the alkali metal includes one or more of metal lithium, metal sodium and metal potassium. When metal lithium is used, a polycyclic aromatic hydrocarbon lithium complex is obtained, when metal sodium is used, a polycyclic aromatic hydrocarbon sodium complex is obtained, and when metal potassium is used, a polycyclic aromatic hydrocarbon potassium complex is obtained, preferably metal lithium is used.
[0052] 102: Soaking polytetrafluoroethylene in the polycyclic aromatic hydrocarbon alkali metal reagent to modify it; washing it with a non-protonic polar solvent, heating and drying it to obtain a modified binder, namely, modified polytetrafluoroethylene powder.
[0053] In step 102, in order to reasonably modify PTFE, as an example, the PTFE is immersed for 1 to 5 minutes. If it is lower than this range, the modification effect may not be achieved or the modification effect may be poor. If it is higher than this range, the PTFE may undergo fundamental structural changes and the fiberization process may be destroyed.
[0054] Among them, when heating and drying, the heating temperature is 100-120°C and the heating time is 6-12h. This range can dry the PTFE. Below this range, it is easy to cause solvent residue, which will cause side reactions during the subsequent charging and discharging process; above this range, it is easy to cause changes in the PTFE structure and affect its adhesion.
[0055] Combination Figure 2 And the following reaction formulas (1) and (2), taking naphthalene, tetrahydrofuran and metallic lithium as examples, the principle of the present application is described in detail:
[0056] After naphthalene is added to tetrahydrofuran, when metallic lithium is added, the lithium transfers the outermost electrons to the empty orbital of naphthalene to form an anion group; then it forms an ion pair with the lithium ion, releases a large amount of resonance energy, and forms a naphthalene-lithium metal organic complex, as shown in reaction formula (1). When polytetrafluoroethylene PTFE is added to the naphthalene-lithium metal organic complex and soaked, the lithium ions in the naphthalene-lithium metal organic complex can destroy the CF bond in the polytetrafluoroethylene PTFE and remove some fluorine atoms on the surface of the polytetrafluoroethylene PTFE, as shown in reaction formula (2) and Figure 2As shown, a carbonized layer and some oxygen-containing functional groups are left on the surface, including polar groups such as hydroxyl, carbonyl and unsaturated bonds. These groups can increase the surface energy, reduce the contact angle and improve the wettability, thereby improving the adhesion of the modified PTFE. When preparing dry electrode plates, the bonding force between the modified PTFE and the conductive agent and the current collector is enhanced, and the problem of insufficient viscoelasticity of PTFE in dry electrode plates is improved. At the same time, the present application destroys some CF bonds in polytetrafluoroethylene PTFE in advance through modification, thereby reducing the generation of interfacial side reaction products, improving the problem of reduced first effect of dry electrodes, and improving battery cycle stability.
[0057]
[0058] It is understandable that other types of polycyclic aromatic hydrocarbons, in combination with non-protonic polar solvents and alkali metals, are used to modify polytetrafluoroethylene (PTFE) in a similar principle to the above principle. They can destroy the CF bonds in polytetrafluoroethylene (PTFE), remove some fluorine atoms on the surface of polytetrafluoroethylene (PTFE), and leave a carbonized layer and some oxygen-containing functional groups on the surface, including polar groups such as hydroxyl, carbonyl and unsaturated bonds. These groups can increase the surface energy, reduce the contact angle, and improve the wettability, thereby improving the adhesion of the modified PTFE. When preparing dry electrode plates, the bonding force between the conductive agent and the current collector is enhanced, and the problem of insufficient viscoelasticity of PTFE in dry electrode plates is improved. At the same time, through modification means, some CF bonds in polytetrafluoroethylene (PTFE) are destroyed in advance, thereby reducing the generation of interfacial side reaction products, improving the problem of reduced first efficiency of dry electrodes, and improving battery cycle stability.
[0059] It is understood that in the present application, the amount of alkali metal added can completely react the polycyclic aromatic hydrocarbons, for example, the alkali metal can be excessive. After the reaction is complete, the excess alkali metal can be separated.
[0060] It can be understood that after polytetrafluoroethylene is immersed in the polycyclic aromatic hydrocarbon alkali metal reagent, the polytetrafluoroethylene is modified, and finally the polycyclic aromatic hydrocarbon alkali metal reagent and the like are washed out by a non-ionic polar solvent, leaving the modified polytetrafluoroethylene powder.
[0061] Taking naphthalene, tetrahydrofuran and metallic lithium as examples, the effect of the concentration of polycyclic aromatic hydrocarbon alkali metal reagents on the modified polytetrafluoroethylene powder is discussed.
[0062] Step S1: in four-hole boiling flask, add a certain amount of refined naphthalene, be placed in dry aluminum pot, load reflux exchanger, thermometer and agitator, then add a certain amount of tetrahydrofuran solution, start agitator.Take a certain amount of metallic lithium, progressively add in four-hole boiling flask, after adding, pass into dry nitrogen, in aluminum pot, inject water, carry out water bath temperature control, temperature is controlled at 15-20 ℃, and the reaction times is 1.5-2h, obtains the solution that naphthalene-lithium complex concentration is respectively 0.3,0.6,0.9,1.2,1.5,1.8mol / L.
[0063] Step S2: PTFE powder is placed in naphthalene-lithium complex solutions of different concentrations and soaked for 2 min under nitrogen protection.
[0064] Step S3: The PTFE soaked in the naphthalene-lithium / tetrahydrofuran solution in step S2 is washed multiple times with tetrahydrofuran, then washed with distilled water, and dried in an oven at 100° C. for 6 h to obtain modified PTFE powder.
[0065] Step S4: The modified PTFE powder obtained under different solution concentrations was tested for tensile shear strength according to GB / T7124-1986 "Test method for tensile shear strength of adhesives". The results are as follows: Figure 3 As shown, the surface contact angle was tested using a contact angle / interfacial tension measuring instrument. The results are shown in Figure 4 shown.
[0066] When the concentration of naphthalene-lithium complex is low, the tensile shear strength of modified PTFE increases with the increase of concentration, and the contact angle decreases with the increase of concentration.
[0067] When the concentration is 0.9 mol / L, the tensile shear strength reaches the maximum value and the contact angle reaches the minimum value.
[0068] When the concentration continues to increase, its tensile shear strength decreases significantly and the contact angle begins to increase. This indicates that when the solution concentration is higher than 0.9 mol / L, the naphthalene-lithium complex has a high reactivity, and the PTFE surface will be subjected to excessive oxidation corrosion, which will cause a coking layer on the surface that is poorly bonded to the bottom layer, thereby reducing the cohesive energy density of the PTFE surface, which is likely to lead to a decrease in tensile shear strength and adhesion.
[0069] Based on this, in the present application, the concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.1 to 2 mol / L. Preferably, the concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.3 to 1.5 mol / L.
[0070] The embodiment of the present application also provides a modified binder for dry-process electrodes, which is prepared using the above-mentioned method for preparing the modified binder for dry-process electrodes.
[0071] Based on the modified binder for dry electrode provided in the above embodiment, see Figure 5 As shown, the embodiment of the present application also provides a method for preparing a dry electrode sheet, which comprises the following steps:
[0072] 201: Premixing the electrode active material, the conductive agent and the modified binder to obtain a premixed powder.
[0073] 202: The premixed powder is subjected to fibrillation treatment to obtain a fiberized material.
[0074] 203: The fiberized material is formed into a film by hot rolling, and then thinned and rolled into a pole film.
[0075] 204: Compounding the electrode film and the current collector by hot rolling to obtain a dry electrode electrode.
[0076] In the preparation method of the dry electrode plate provided in the present application, there is no need to add NMP solvent, thus avoiding the emission and residue of toxic gases, and there is no need for an oven and NMP recovery device required in the wet coating process, which effectively reduces the manufacturing cost of the battery and complies with the concept of green environmental protection, cost reduction and energy saving.
[0077] In the above step 201, according to the mass fraction, the electrode active material is 80% to 99%, the conductive agent is 0.5% to 10%, and the modified binder is 0.5% to 10%.
[0078] Wherein, the electrode active material is a positive electrode active material or a negative electrode active material.
[0079] The positive electrode active material includes a mixture of one or more of lithium iron phosphate LFP, lithium iron manganese phosphate LFMP, lithium nickel cobalt manganese oxide NCM, lithium cobalt oxide LCO, lithium nickel manganese oxide LNMO and lithium-rich manganese-based LRM.
[0080] The negative electrode active material includes one or more of graphite or silicon carbon.
[0081] The conductive agent includes one or more of carbon nanotubes CNT, acetylene black, SuperP, Ketjen black, MXene and graphene.
[0082] In the above step 201, during premixing, the rotation speed is 1000-2500 rpm and the mixing time is 10-30 min. If it is lower than this range, the mixing uniformity will be insufficient, and if it is higher than this range, the particles will be easily damaged, which will affect the subsequent electrical performance.
[0083] In the above step 202, the fibrillation treatment is carried out in the form of one or more of a mortar, a high mixer and a jet mill. Preferably, the fibrillation treatment is carried out by a jet mill, and the airflow pressure during the feeding of the jet mill is 0.6-0.8Mpa, and the crushing pressure is 0.4-0.6Mpa. If the pressure is lower than this range, the PTFE cannot be completely fibrillated, affecting its adhesion. If the pressure exceeds this range, the particles are easily damaged, affecting the electrical properties. The crushing pressure changes from large to small, that is, when the fibrillation treatment is carried out, the crushing pressure gradually decreases from 0.6Mpa to 0.4Mpa.
[0084] If the roller surface temperature and pressure are too low during the hot roller pressing film forming and thinning process, the film cannot be formed; if the temperature is too high, the electrode structure will be damaged and the electrical performance will be affected; if the film is too thin, the energy density will be very low; if it is too thick, the ion transmission path will be longer and the rate cycle performance will be affected. Therefore, as a preferred example, in the above step 203, the roller surface temperature during the hot roller pressing film forming and thinning process is 60-150°C, the roller pressure is 200-2000kg, and the thickness of the thinned electrode film is 50-300um; the hot roller pressing film forming and thinning process includes one or more of transverse rolling, longitudinal rolling, and alternating transverse and longitudinal directions.
[0085] If the temperature and pressure are too low during the hot rolling lamination process, the film cannot be formed, and if the temperature and pressure are too high, the electrode structure will be damaged and the electrical performance will be affected. Therefore, as a preferred example, in the above step 204, the temperature during the hot rolling lamination process is 80-200°C and the pressure is 200-2000kg.
[0086] The current collector is one of carbon-coated copper foil, carbon-coated aluminum foil, perforated aluminum foil or perforated copper foil.
[0087] The embodiment of the present application also provides a dry electrode plate, which is prepared using the above-mentioned method for preparing the dry electrode plate.
[0088] The embodiment of the present application further provides a secondary battery, which includes the above-mentioned dry electrode plate. The secondary battery is a lithium ion battery, a sodium ion battery, a magnesium ion battery, a potassium ion battery or a zinc ion battery.
[0089] The present application is described in detail below through examples and comparative examples.
[0090] Embodiment 1:
[0091] The specific preparation process of dry positive electrode is as follows:
[0092] (1) Add 5.1g of refined naphthalene to a four-necked flask, place it in a dry aluminum pot, install a reflux condenser, a thermometer and a stirrer, then add 100g of tetrahydrofuran solution and start the stirrer. Take excess lithium metal and gradually add it to the four-necked flask. After the addition, introduce dry nitrogen, inject water into the aluminum pot, control the temperature at 15-20°C, and react for 1.5-2h to obtain a naphthalene-lithium / tetrahydrofuran solution with a concentration of 0.4mol / L;
[0093] (2) Soaking the PTFE powder in a naphthalene-lithium / tetrahydrofuran solution for 2 min under nitrogen protection;
[0094] (3) washing the PTFE soaked in the naphthalene-lithium / tetrahydrofuran solution in step S2 for multiple times with tetrahydrofuran, then washing with distilled water, and drying in an oven at 100° C. for 6 h to obtain modified PTFE powder;
[0095] (4) premixing the positive electrode active material NCM811, the conductive agent SP (i.e., SuperP), and the modified PTFE powder in step (3) at a mass ratio of 95:2:3 using a mixer at a speed of 1000 rpm for 30 minutes under an inert atmosphere to obtain a mixture;
[0096] (5) The mixture in step (4) is subjected to fibrillation treatment by feeding the mixture through a jet mill, wherein the air flow pressure during feeding is 0.6 MPa, and the crushing pressure is gradually reduced from 0.6 MPa to 0.4 MPa at a rate of 0.1 MPa per minute;
[0097] (6) The fibrillated material of step (5) is hot rolled at 80°C and 1000kg rolling pressure to form a film, and after multiple thinning, it is rolled into a 200um thick electrode film. The electrode film and 12um thick aluminum current collector are hot rolled at 100°C and 500kg rolling pressure to obtain a dry positive electrode.
[0098] Wet negative electrode sheet preparation process:
[0099] The negative electrode active material graphite, conductive agent SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are added to deionized water in a mass ratio of 95:1.5:1.5:2, mixed evenly in a mixing tank to obtain a negative electrode slurry, and wet-coated, dried, and rolled to obtain a wet-process negative electrode sheet.
[0100] The positive and negative electrode sheets are subjected to sheeting, lamination, top and side sealing, vacuum drying, liquid injection, standing, formation, and capacity separation to obtain a soft-pack battery.
[0101] Embodiment 2:
[0102] 12.8 g of naphthalene was dissolved in 100 g of tetrahydrofuran solvent, and then an excess of metallic lithium was added to form naphthalene-lithium to obtain a naphthalene-lithium solution with a concentration of 1.0 mol / L. The rest was the same as in Example 1.
[0103] Embodiment 3:
[0104] 25.6 g of naphthalene was dissolved in 100 g of tetrahydrofuran solvent, and then an excess of metallic lithium was added to form naphthalene-lithium to obtain a naphthalene-lithium solution with a concentration of 2 mol / L. The rest was the same as in Example 1.
[0105] Embodiment 4:
[0106] 15.4 g of biphenyl was dissolved in 100 g of acetone solvent, and then an excess of metallic lithium was added to form biphenyl-lithium to obtain a biphenyl-lithium solution with a concentration of 1.0 mol / L. The rest was the same as in Example 1.
[0107] Embodiment 5:
[0108] Wet-process positive electrode sheet preparation process:
[0109] The positive electrode active material NCM811, the conductive agent SP, and polyvinylidene fluoride (PVDF) are added to the NMP solvent in a mass ratio of 95:2:3, and mixed evenly in a mixing tank to obtain a positive electrode slurry, which is then wet-coated, dried, and rolled to obtain a wet-process positive electrode sheet.
[0110] Dry negative electrode sheet preparation process:
[0111] (1) Add 12.8g of refined naphthalene to a four-necked flask, place it in a dry aluminum pot, install a reflux condenser, a thermometer and a stirrer, then add 100g of tetrahydrofuran solution and start the stirrer. Take excess metallic lithium and gradually add it to the four-necked flask. After the addition is complete, introduce dry nitrogen, inject water into the aluminum pot, control the temperature at 15-20°C, and react for 1.5-2h to obtain a naphthalene-lithium / tetrahydrofuran solution with a concentration of 1.0 mol / L;
[0112] (2) Soaking the PTFE powder in a naphthalene-lithium / tetrahydrofuran solution for 2 min under nitrogen protection;
[0113] (3) washing the PTFE soaked in the naphthalene-lithium / tetrahydrofuran solution in step S2 for multiple times with tetrahydrofuran, then washing with distilled water, and drying in an oven at 100° C. for 6 h to obtain modified PTFE powder;
[0114] (4) Premixing the negative electrode active material graphite, the conductive agent SP, and the modified PTFE powder in step (3) at a mass ratio of 95:2:3 using a mixer at a speed of 1000 rpm for 30 minutes under an inert atmosphere to obtain a mixture;
[0115] (5) The mixture in step (4) is subjected to fibrillation treatment by feeding the mixture through a jet mill, wherein the air flow pressure during feeding is 0.6 MPa, and the crushing pressure is gradually reduced from 0.6 MPa to 0.4 MPa at a rate of 0.1 MPa per minute;
[0116] (6) The fibrillated material in step (5) is hot rolled at 80° C. and 1000 kg rolling pressure to form a film, and after multiple thinning, it is rolled into a pole piece film with a thickness of 120 μm. The pole piece film and a 6 μm thick copper current collector are hot rolled and composited at 100° C. and 500 kg rolling pressure to obtain a dry-process negative pole piece.
[0117] The positive and negative electrode sheets are subjected to sheeting, lamination, top and side sealing, vacuum drying, liquid injection, standing, formation, and capacity separation to obtain a soft-pack battery.
[0118] Embodiment 6:
[0119] A dry-process positive electrode sheet was prepared according to the method of Example 2, and a dry-process negative electrode sheet was prepared according to the method of Example 5.
[0120] The positive and negative electrode sheets are subjected to sheeting, lamination, top and side sealing, vacuum drying, liquid injection, standing, formation, and capacity separation to obtain a soft-pack battery.
[0121] Comparative Example 1:
[0122] A wet-process negative electrode sheet was prepared according to the method of Example 1, and a wet-process positive electrode sheet was prepared according to the method of Example 5.
[0123] The positive and negative electrode sheets are subjected to sheeting, lamination, top and side sealing, vacuum drying, liquid injection, standing, formation, and capacity separation to obtain a soft-pack battery.
[0124] Comparative Example 2:
[0125] Ordinary dry cathode electrode preparation process:
[0126] (1) The positive electrode active material NCM811, the conductive agent SP, and the PTFE were pre-mixed in a mass ratio of 95:2:3 using a mixer at a rotation speed of 1000 rpm for 30 minutes under an inert atmosphere to obtain a mixture;
[0127] (2) fibrillating the mixture in step (1) by feeding it through a jet mill, wherein the airflow pressure during feeding is 0.6 MPa, and the crushing pressure is gradually reduced from 0.6 MPa to 0.4 MPa at a rate of 0.1 MPa per minute;
[0128] (3) The fibrillated material in step (2) is hot rolled at 80°C and 1000kg rolling pressure to form a film, and after multiple thinning, it is rolled into a 200um thick electrode film. The electrode film and a 12um thick aluminum current collector are hot rolled and composited at 100°C and 500kg rolling pressure to obtain a dry-process positive electrode.
[0129] Ordinary dry negative electrode preparation process:
[0130] (1) Premixing the negative electrode active material graphite, the conductive agent SP, and the PTFE in a mass ratio of 95:2:3 using a mixer at a rotation speed of 1000 rpm for 30 minutes under an inert atmosphere to obtain a mixture;
[0131] (2) fibrillating the mixture in step (1) by feeding it through a jet mill, wherein the airflow pressure during feeding is 0.6 MPa, and the crushing pressure is gradually reduced from 0.6 MPa to 0.4 MPa at a rate of 0.1 MPa per minute;
[0132] (3) The fibrillated material in step (2) is hot rolled at 80° C. and 1000 kg rolling pressure to form a film, and after multiple thinning, it is rolled into a pole piece film with a thickness of 120 μm. The pole piece film and a 6 μm thick copper current collector are hot rolled and composited at 100° C. and 500 kg rolling pressure to obtain a dry-process negative pole piece.
[0133] The positive and negative electrode sheets are subjected to sheeting, lamination, top and side sealing, vacuum drying, liquid injection, standing, formation, and capacity separation to obtain a soft-pack battery.
[0134] The above-mentioned electrode was subjected to a peeling force test. A long strip electrode sample with a sample width of 15 mm was adhered parallel to a stainless steel plate by a pressure-sensitive tape. The stainless steel plate and the current collector were fixed on two fixtures of a universal testing machine to ensure that the electrode and the tensile force were in a vertical direction. The applied load was 10 N, the tensile speed was 100 mm / min, and the peeling strength was measured after 180° peeling.
[0135] The electrochemical performance test of the above-mentioned soft-pack battery was carried out with a test voltage window of 2.8-4.3V (vsLi / Li+), and continuous charge and discharge tests were carried out at a current rate of 1C.
[0136] Table 1 shows the electrochemical properties of the soft-pack lithium-ion batteries corresponding to Examples 1-6 and Comparative Examples 1-2.
[0137] Table 1
[0138]
[0139]
[0140] It can be seen from Table 1 that the positive and negative dry-process electrode sheets prepared by the method of the present application in Examples 1 to 6 have higher peeling force than the wet-process electrode sheets in Comparative Example 1 and the unmodified dry-process electrode sheets in Comparative Example 2, and the bonding performance of the surface sheets is improved to a certain extent, indicating that the modified PTFE improves the contact between the active material and the conductive agent and the current collector.
[0141] Example 2 and Example 3 adopt the preparation method of Example 1, except that the concentration of modified naphthalene-lithium is increased from 0.4 mol / L to 1.0 mol / L and 2 mol / L, wherein Example 2 has improved positive electrode sheet peeling force and electrical performance compared with Example 1, indicating that appropriate modification is beneficial to battery performance, while Example 3 has decreased instead of increased, indicating that excessive modification causes fundamental changes in the PTFE structure, but weakens its fibrosis characteristics. Therefore, preferably, the concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.3 to 1.5 mol / L.
[0142] Example 4 adopts the preparation method of Example 2, except that naphthalene is replaced by biphenyl, and the polar solvent tetrahydrofuran is replaced by acetone. After the replacement, compared with Example 1, the electrode adhesion and battery performance are improved, indicating that other polycyclic aromatic hydrocarbon modification systems can also modify PTFE.
[0143] In Examples 5 and 6, modified dry-process negative electrode sheets were introduced, and the first efficiency and cycle performance of the battery were further improved, indicating that this modified PTFE is also suitable for the negative electrode system.
[0144] From the above conclusions, it can be seen that the bonding performance of modified PTFE is improved, some CF bonds are destroyed in advance, the degree of interfacial side reactions is reduced, the problem of reduced initial efficiency of dry electrodes and subsequent cycle stability is improved, and it can be applied to both positive and negative electrode systems, and has certain industrial value.
[0145] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a modified binder for a dry electrode, characterized in that: It includes: The polycyclic aromatic hydrocarbons are dissolved in a non-protonic polar solvent, and an alkali metal is added to generate a polycyclic aromatic hydrocarbon alkali metal reagent; The polytetrafluoroethylene is immersed in the polycyclic aromatic hydrocarbon alkali metal reagent to be modified; the polytetrafluoroethylene immersed in the polycyclic aromatic hydrocarbon alkali metal reagent is washed with a non-protonic polar solvent, and then heated and dried to obtain modified polytetrafluoroethylene powder.
2. The method for preparing a modified binder for a dry electrode according to claim 1, characterized in that: The polycyclic aromatic hydrocarbons include one or more of naphthalene, biphenyl, biphenyls, and condensed ring aromatic hydrocarbons.
3. The method for preparing a modified binder for a dry electrode according to claim 1, characterized in that: The aprotic polar solvent includes one or more of dimethylformamide, dimethyl sulfoxide, acetone, tetrahydrofuran and dimethyl ether.
4. The method for preparing a modified binder for a dry electrode according to claim 1, characterized in that: The alkali metal includes one or more of metallic lithium, metallic sodium and metallic potassium.
5. The method for preparing a modified binder for a dry electrode according to claim 1, characterized in that: The concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.1-2 mol / L.
6. The method for preparing a modified binder for a dry electrode according to claim 5, characterized in that: The concentration of the polycyclic aromatic hydrocarbon alkali metal reagent is 0.3-1.5 mol / L.
7. The method for preparing a modified binder for a dry electrode according to claim 1, characterized in that: The polytetrafluoroethylene is immersed for 1 to 5 minutes.
8. The method for preparing a modified binder for a dry electrode according to claim 1, characterized in that: When heating and drying, the heating temperature is 100-120°C and the heating time is 6-12h.
9. A modified binder for dry process electrodes, characterized in that: The modified binder is prepared by the method for preparing a modified binder for a dry electrode as described in any one of claims 1 to 8.
10. A method for preparing a dry electrode sheet, characterized in that: It includes: Premixing the electrode active material, the conductive agent and the modified binder for the dry electrode as claimed in claim 9 to obtain a premixed powder; The premixed powder is subjected to fibrillation treatment to obtain a fiberized material; The fiberized material is pressed into a film by hot rollers, and then thinned and rolled into a pole film; The electrode film and the current collector are composited by hot rolling to obtain a dry electrode electrode.
11. The method for preparing a dry electrode sheet according to claim 10, characterized in that: Calculated by mass fraction, the electrode active material is 80% to 99%, the conductive agent is 0.5% to 10%, and the modified binder is 0.5% to 10%.
12. The method for preparing a dry electrode sheet according to claim 10, characterized in that: The electrode active material is a positive electrode active material or a negative electrode active material.
13. The method for preparing a dry electrode sheet according to claim 12, characterized in that: The positive electrode active material includes a mixture of one or more of lithium iron phosphate LFP, lithium iron manganese phosphate LFMP, lithium nickel cobalt manganese oxide NCM, lithium cobalt oxide LCO, lithium nickel manganese oxide LNMO and lithium-rich manganese-based LRM.
14. The method for preparing a dry electrode sheet according to claim 12, characterized in that: The negative electrode active material includes one or more of graphite or silicon carbon.
15. The method for preparing a dry electrode sheet according to claim 12, characterized in that: The conductive agent includes one or more of carbon nanotubes CNT, acetylene black, SuperP, Ketjen black, MXene and graphene.
16. The method for preparing a dry electrode sheet according to claim 10, characterized in that: During premixing, the rotation speed is 1000-2500 rpm and the mixing time is 10-30 minutes.
17. The method for preparing a dry electrode sheet according to claim 10, characterized in that: The fibrillation treatment is carried out by using a jet mill, the air flow pressure when feeding the jet mill is 0.6-0.8Mpa, the crushing pressure is 0.4-0.6Mpa, and the crushing pressure changes from large to small.
18. The method for preparing a dry electrode sheet according to claim 10, characterized in that: The roller surface temperature during the hot roller pressing film forming and thinning process is 60-150°C, the roller pressing pressure is 200-2000kg, and the thinned electrode film thickness is 50-300um; the hot roller pressing film forming and thinning process includes one or more of transverse rolling, longitudinal rolling, and alternating transverse and longitudinal rolling.
19. The method for preparing a dry electrode sheet according to claim 10, characterized in that: The temperature during the hot roller pressing composite process is 80-200°C and the pressure is 200-2000kg.
20. A dry electrode plate, characterized in that: It is prepared by the dry electrode sheet preparation method as described in any one of claims 10 to 19.
21. A secondary battery, characterized in that: It includes the dry electrode plate as described in claim 20.
Citation Information
Cited By
Preparation method of dry-method pole piece
CN119864375A
Preparation method of lithium iron manganese phosphate positive electrode material by coprecipitation method
CN120463170A
Preparation method of lithium manganese iron phosphate cathode material by co-precipitation
CN120463170B